2017
DOI: 10.1002/hup.2596
|View full text |Cite
|
Sign up to set email alerts
|

A market on both “sides” of the law: The use of the hidden web for the sale of new psychoactive substances

Abstract: Vendors selling and availability of NPS increased over the 12 months of data collection. Potential displacement from the visible Web to hidden Web should be taken into consideration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…The crypto markets present over the 12 months of data collection fluctuated because of crypto markets opening, adding NPS to their sales, or closing following exit scams or law enforcement. A table of the crypto markets included in this study can be found elsewhere [ 27 ].…”
Section: Methodsmentioning
confidence: 99%
“…The crypto markets present over the 12 months of data collection fluctuated because of crypto markets opening, adding NPS to their sales, or closing following exit scams or law enforcement. A table of the crypto markets included in this study can be found elsewhere [ 27 ].…”
Section: Methodsmentioning
confidence: 99%
“…Cryptomarket and the Dark Web: 2016 Wholesale of drugs on the cryptomarket [ 1611 ]; Norwegian study examining the role of online drug communities in the development of new drug trends (focus on synthetic cannabinoids) [ 1612 ]; role of the dark web in social marketing heroin [ 1613 ]; purity data for 219 samples purchased from the cryptomarket and analyzed by GC/MS [ 1614 ]; study of the online illicit drug market through the analysis of digital, physical and chemical data [ 1615 ]; Characterization of dark net marketplace purchasers [ 1616 ]; study documenting NPS for sale on the Tor site (Agora) from February to June 2015 [ 1617 ]; overview of the Canadian illicit drug market including the most prevalent illicit drugs vendors offer for sale and preferred destination countries [ 1618 ]; overview of internet sales of counterfeit medicines in Slovenia [ 1619 ]; use of a Python scripts to extract information about listings and sellers of illicit drug products online revealed more than 48,000 listings and 2700 vendors in 70 countries [ 1615 ]; case reports of heroin purchased from Craigslist [ 1620 ]; study of consumer motivations for purchasing illicit substances on the dark net [ 1616 ]; 2017 overview of on-line drug purchases and comparison of on-line with off-line purchased drugs regarding purity, adulteration and price through laboratory analyses of 32663 drug consumer samples (stimulants and hallucinogens) purchased between January 2013 and January 2016–928 of which were bought on-line [ 1621 ]; forensic drug intelligence through the study of the Australian virtual cryptomarket [ 1622 ]; trends in market dynamics of NPS within cryptomarkets [ 1623 ]; comparison of drug-related information posted on Pillreports.net and Partyflock.nl between January 1, 2014 and December 31, 2015 to actual concentration found in ecstasy tablets were investigated for accuracy [ 1624 ]; analysis of the Australian cryptomarket in regard to drug products available for purchase and prices [ 1625 ]; study of buyers of illegal product from cryptomarkets focused on loyalty and repeat buyers [ 1626 ]; impact of online drug market [ 1627 ]; impact of the Psychoactive Substances Act (UK) on the availability of the synthetic cannabinoid receptor agonist MDMB-CHMICA from online suppliers [ 1628 ]; evaluation of the online market of non-prescription somatropin products [ 198 ]; review of the NPS market on the visible and hidden Web [ 1629 ]; 2018 natural language processing and machine learning to identify NPS and correlate patterns of co-mentions of substances across posts in online forums [ 1630 ]; data collected from a large e-commerce website for drugs over 305 days in 2014 and 2015 documents that drug dealers give away samples of all major substance categories and samp...…”
Section: Miscellaneous Topicsmentioning
confidence: 99%
“…shops and an open source of NPS, but has driven the market for NPS to the clandestine street market alongside traditional drugs such as amphetamine, cannabis, cocaine and heroin (Shapiro and Daly, 2017), as well as to the deeper recesses of the Internet. Wadsworth et al (2017) report a possible shift of cathinone sales in the UK from the surface web to the deep web, following the coming into effect of the Psychoactive Substances Act 2016 on 26 May 2016.…”
Section: 21: Legal Status Of Cathinonesmentioning
confidence: 99%